Occurrence of form PIIcf sieve-element plastids in Xyris species (Xyridaceae) - Machado, S. R. [UNESP]; Sajo, M. G. [UNESP] (Oxford University Press (OUP), 1996)
Mature leaf fragments from eight species of Xyris from the Serra do Cipo, State of Minas Gerais, Brazil, were prepared by the usual methods for electron microscopy. Ultrastructural analysis of phloem shows the occurrence of nacreous walls with a polylamellate structure in the sieve-elements of X. tortilis and plastids similar to P-plastids, form PIIcf in the sieve-elements of all investigated species.
Keywords: monocotyledons; Sieve-element plastids; Xyris; Liliopsida; Xyridaceae